Safranal Alleviates Cyclophosphamide Induced Testicular Toxicity in Rats - Cellat, Mustafa; Yavaş, İlker; Uyar, Ahmet; Etyemez, Muhammed; Güvenç, Mehmet (Wiley, 2025)
ABSTRACTSafranal, the principal component of Crocus sativus essential oil, is primarily responsible for the characteristic aroma and distinct odor of saffron. Cyclophosphamide (CP), a chemotherapeutic agent commonly used in the treatment of both malignant and non‐malignant conditions, is known to induce cytotoxicity in various tissues, particularly within the male reproductive system. This study aimed to investigate the protective effects of safranal against CP‐induced reproductive toxicity in Wistar albino rats. CP was administered orally at a dose of 15 mg/kg once per week for 56 days to establish a model of testicular toxicity. In parallel, the treatment group received safranal via oral gavage at a daily dose of 200 mg/kg for the same duration. At the end of the treatment period, spermatological, biochemical, and histological analyses were performed on collected tissue samples. CP administration led to increased dead/live and abnormal sperm ratios, elevated levels of NF‐κB, IL‐6, TNF‐α, and MDA, and a reduction in sperm motility and density, Nrf‐2 expression, as well as GSH and GSH‐Px activity. In contrast, safranal treatment significantly ameliorated these detrimental effects. In conclusion, safranal demonstrated protective and therapeutic effects against CP‐induced reproductive toxicity, suggesting its potential as a supportive agent during chemotherapy.
Keywords: Original Article